Desenho de contrato para construção e gerenciamento de obras públicas com provisão pública e privada: uma aplicação de teoria dos contratos incompletos - Costa, Antonio Kassyo Monteiro (2022)
The purpose of this paper is to present an incomplete contract model that captures the relationship between the public and private sectors, in the sense that the public sector contracts private companies in bundling (Consortium) or separate companies (Conventional Provision) to buildand manage a facility with government ownership. The central problem is to be able to present a model that the government can control the decision related to the delay of infrastructureconstruction due to unforeseen contingencies in contracts, associated with increased costs inconstruction. It is considered that the delay in the construction is related to an increase incosts in the management phase of the facility, so the increase in the cost of the management phase is considered an externality of the construction process. The idea is to internalize this externality between the construction and management processes for the construction firm or for the government. The study is based on previous work such as those by Hart et al. (1997), Hart (2003) and Bennett and Iossa (2006). The model internalizes the externality through a methodology of payment incentives in the contract due to a renegotiation between the governmentand the construction firm, in case there are cost contingencies, thus giving control of the processto the asset owner.